Rocket missile lift-off and flight simulator program - Dziopa, Zbigniew (Computer Assisted Methods in Engineering and Science; Vol 7 No 4 (2000), 2023)
The subject of this paper is a movable antiaircraft short-range rocket set. The control algorithm for a target homing short-range rocket missile by means of the proportional approach method is performed by an executive system comprising the co-ordinator and automatic pilot devices. The co-ordinator is equipped with a gyro-device and a system determining working out of the ideal, desirable signal. The automatic pilot device has a pair of double-position external vanes and internal gas control engine. A missile control, in accordance with the implemented algorithm, is achieved by using a rocket rotating motion around its longitudinal axis